Effects of domain manipulation in the Staphylococcal Phage 88 endolysin on lytic efficiency and host range - Krishnan, Melvina Mayuri (2024)
Endolysins are bacteriophage (phage) lytic enzymes responsible for phage-mediated lysis of bacterial peptidoglycan (PGN). Phage therapy for Multidrug-Resistant Staphylococcus aureus (MDRSA) infections is currently emerging due to antibiotic resistance. However, using whole phages for therapy has presented several drawbacks including resistance by the bacterial host hence the use of phage endolysins instead. Staphylococcal phage endolysins typically consist of two types of domains: Enzymatically-Active Domains (EAD) and Cell Wall-Binding Domain(s) (CBD). The EADs cleave PGN whereas the CBD localizes endolysins to PGN. The Staphylococcal Phage 88 endolysin (NXEndo88) consists of two EADS: an N-terminal Cysteine, Histidine-dependent Amidohydrolase/Peptidase (CHAP) domain and a central Amidase-2 domain, as well as one CBD: a C-terminal Src Homology 3b (SH3b) domain. The host strain of the phage is Staphylococcus aureus PS88, an MDRSA. Domain manipulations encompassing truncations and swapping among different endolysins have been shown to alter endolysin lytic efficiency and host range. Therefore, the purpose of this study was to determine the effects of domain manipulations on the lytic efficiency and host range of NXEndo88. Five mutants were generated – three truncation mutants: 1) CHAP, 2) CHAPAmidase and 3) CHAPSH3; and two chimera mutants containing the tandem Cpl7 CBDs from a streptococcal endolysin, LambdaSa2-ECC: 4) CHAPAmidase-Cpl7Cpl7 and 5) Endo88-Cpl7Cpl7. The protein constructs were cloned into the pET28a plasmid vector and expressed in E. coli BL21(DE3). Proteins were then purified using Nickel-Nitrilotriacetic Acid (NTA) affinity chromatography for His-tagged proteins. Host range and lytic efficiency were subsequently assessed via plate lysis assays and turbidity reduction assays. All truncated mutants exhibited reduced lytic activity compared to NXEndo88 towards the host strain, Staphylococcus aureus PS88. The same pattern was observed in three other staphylococci (Staphylococcus aureus Mu50, Staphylococcus epidermidis and Staphylococcus hominis) as well as Enterococcus faecalis. Outside these two bacterial genera, no lytic activity was detected. The CHAPAmidase and CHAPSH3 constructs exhibited varying specific activities between S. aureus PS88 and S. epidermidis, which may be attributed to strain-specific PGN features. Next, the chimera mutants (CHAPAmidase-Cpl7Cpl7 and Endo88-Cpl7Cpl7) were tested against two strains, S. aureus PS88 and Streptococcus agalactiae, as the addition of the Cpl7Cpl7 domains (specific to streptococci) were predicted to extend their host range to lyse streptococci. However, lytic activity was only detected against S. aureus PS88. Both chimeras had reduced lytic activity compared to NXEndo88, which may be attributed to structural instability. In conclusion, all domains of the NXEndo88 endolysin are interdependent for maximum lytic efficiency, where removal of Amidase-2 and/or SH3b reduced lytic efficiency. As for the chimera constructs, it appears that swapping or adding the Cpl7 CBDs from a streptococcal endolysin was insufficient to expand the host range. Multi-faceted studies on the factors influencing endolysin functionality are necessary for the development and optimization of targeted antimicrobials against MDRSA.